The Impact of BUMDes on Poverty in Pamekasan Regency - Putra, Aji Muharjana; Idialis, Alifah Rokhmah (Universitas Muhammadiyah Sorong, 2025)
Rural poverty in Pamekasan Regency remains a significant structural challenge in East Java. One of the government's strategies to address it is through strengthening the role of Village-Owned Enterprises (BUMDes) as community-based economic and social institutions. This study aims to analyze the effect of BUMDes' role on individual poverty levels in Pamekasan Regency. A quantitative approach with Ordinal Logistic Regression analysis was used to evaluate three roles of BUMDes, namely contribution to income generation, expansion of access to employment, and provision of economic and social services. Primary data was obtained through a survey of 85 respondents involved with BUMDes in a number of villages. The results of the analysis show that all three variables have a significant effect on the likelihood of individuals being at a lower poverty level. This finding confirms that the strategic role of BUMDes in income generation, employment generation, and provision of quality services can promote poverty alleviation at the village level. Based on these findings, village development policies should be directed towards strengthening the function of BUMDes through the development of inclusive business units, increasing the capacity of BUMDes in providing local employment opportunities, as well as providing relevant and community welfare-oriented services.